Health systems in the news: The influence of media representations on health system functioning in the Western Cape health system - Gopal, Thania (Department of Public Health and Family Medicine, 2019)
Health systems are complex systems characterised by constant change and a web of interwoven relationships, connections, and interactions. Health Policy and Systems Research has called for multidisciplinary approaches to understanding health systems. Like health systems, the media has also been described as an important social institution in modern society that is deeply embedded within the sociocultural and political context. The role of the media as societal watchdog; as a mechanism to improve accountability; as a platform for debate; and as a facilitator of community engagement has been recognised. Within public health, the role of mass media as a tool in health promotion and health communication campaigns is well-established. Media representation research involves the analysis of discourses in media and has been used to study a range of public health issues. However, there is a major gap in representation studies of health systems, in high-, middle- and low income countries. This mixed methods study aimed to describe representations of the South African Western Cape provincial health system by analysing dominant discourses emerging from the English-language mainstream print and online news media (1994-2018). A media content analysis was first conducted to highlight the main themes, followed by a discourse analysis to provide a deeper interrogation of underlying issues. This study suggests that the way a health system is represented in the media potentially influences health system functioning in a variety of ways – for example, how ‘people’ in the system make meaning of discourses, which in turn influences decision-making. ‘Negative’ representations (for example, of a weak or stressed health system), may contribute to a lack of both health worker and patient trust in the health system with a host of undesirable repercussions, such as low health worker morale, health workers failing to speak up for patients, or poor quality of care. The study recommends capacity building of a diversity of people (such as citizens, communities, health workers, civil society) at different levels of the health system to enable them to engage with the media, and mitigate the less desirable repercussions. Further research is needed to, a) consider the effects of media on health systems more carefully, more frequently, and in more contexts; b) find more effective ways to think of media as part of the health system, rather than an instrumental tool, or an external influence; c) to understand how media architecture (the social, political and economic environment in which media are situated) may influence emerging discourses; and d) to understand how media can influence people’s agency and community participation, particularly in the context of responsive and people-centred health systems.